Isolation and Characterization of Starch from Moth Bean - Kevate, B.N.; Chavan, U.D.; Kadam, S.S.; Chavan, J.K.; Amarowicz, R. (Global Journal of Food and Agribusiness Management, 2011)
The dry seeds contained 47.9% starch. The starch was isolated from seeds using cold water, hot water and alkali solution (NaOH, 1.5%) as extractant with 28.1, 32.8 and 29.9%, recovery respectively. The purified starch contained 0.06% nitrogen, 0.09% ash, and 0.16% lipids. The isolated starch contained 27% amylose with 4.0%-damaged starch. Water and fat absorption capacity and gelatinization temperature of isolated starch were 80.2%, 72.5% and 66.5 0 C, respectively. Swelling factor increased from 1.7% at 50 0 C to 21.4% at 95 0 C while amylose leaching was observed above 70 0 C (7.7%) and it was maximum 14.4% at 95 0 C. Enzymatic hydrolysis within 24 hr was 24.9% while the acid hydrolysis observed upto 40.1% within 20 days.